2011
DOI: 10.1124/jpet.111.186775
|View full text |Cite
|
Sign up to set email alerts
|

Histone H3 Phosphorylation (Ser10, Ser28) and Phosphoacetylation (K9S10) Are Differentially Associated with Gene Expression in Liver of Rats Treated In Vivo with Acute Ethanol

Abstract: The epigenetic histone modification by ethanol is emerging as one of the mechanisms for its deleterious effects in the liver. In this context, we have investigated the role of histone H3 phosphorylation at Ser10 (P-H3-Ser10), and Ser28 (P-H3-Ser28) in liver after acute ethanol treatment in vivo. Ethanol was administered intraperitoneally in male Sprague-Dawley rats. Ethanol dose-response (1-5 g/kg body weight) and time-course (1-4 h) experiments were conducted, and various parameters were monitored. Steatosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 39 publications
(48 reference statements)
2
25
0
Order By: Relevance
“…Recently, it has been reported that alcohol exposure alters chromatin signatures, which results in genetic and phenotypic changes [21][22][23]. In the present study, we also found that some chromatin modifiers were altered under binge alcohol consumption.…”
Section: Epigenetic Changes Related To Ethanol Exposure During Pregnancysupporting
confidence: 76%
“…Recently, it has been reported that alcohol exposure alters chromatin signatures, which results in genetic and phenotypic changes [21][22][23]. In the present study, we also found that some chromatin modifiers were altered under binge alcohol consumption.…”
Section: Epigenetic Changes Related To Ethanol Exposure During Pregnancysupporting
confidence: 76%
“…In primary hepatocytes ethanol increased histone H3 phosphorylation at serine 10 and serine 28 residues ; this has also been shown to occur in vivo (James et al, 2012). Furthermore, ethanol in vivo caused increases in the dually modified histone H3, i.e., H3AcK9 and H3AcK9 phosphorylated at serine 10 (James et al, 2012;Aroor et al, 2014). Whether this unique dual modification also occurs in primary hepatocytes remained unknown.…”
Section: Actions Of Ethanol and Acetate In Hepatocytes Resultsmentioning
confidence: 99%
“…In contrast, the antioxidant N-acetyl cystein (NAC) neutralized ethanol-induced global acetylation on H3K9 in hepatocytes (Choudhury et al , 2010). Several other groups also reported that histone modifications (acetylation, methylation, and phosphorylation) were involved in gene regulation in alcoholic liver diseases (Ghezzi et al , 2013, James et al , 2012, Pal-Bhadra et al , 2007. p300, a HAT, was up-regulated in alcohol-fed rat livers to stimulate H3K9acetylation ( Bardag-Gorce et al , 2007).…”
Section: Histone Modification and Alcohol-induced Liver Injurymentioning
confidence: 88%